2020
DOI: 10.1002/14651858.cd012022.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic models for newly-diagnosed chronic lymphocytic leukaemia in adults: a systematic review and meta-analysis

Abstract: Prognostic models for newly-diagnosed chronic lymphocytic leukaemia in adults: a systematic review and meta-analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 300 publications
0
33
0
Order By: Relevance
“…5 We are aware, however, that the model may integrate but not replace clinical expertise and medical judgment. 6,7…”
Section: Prognostic Models In Chronic Lymphocytic Leukemia Patients Receiving Ibrutinib Therapy: Results Of a Comparative Performance Anamentioning
confidence: 99%
“…5 We are aware, however, that the model may integrate but not replace clinical expertise and medical judgment. 6,7…”
Section: Prognostic Models In Chronic Lymphocytic Leukemia Patients Receiving Ibrutinib Therapy: Results Of a Comparative Performance Anamentioning
confidence: 99%
“…Several prognostic algorithms derived from multivariable models, nomograms and score systems have been developed to predict clinical outcomes accurately in early-stage CLL ( 64 ). The IGHV gene configuration is one of the most important single factors predicting therapy need, and it is recurrently incorporated in all prognostic models ( 65 ).…”
Section: Discussionmentioning
confidence: 99%
“…It consists of four domains: participants, predictors, outcome, and analysis, and includes twenty specific items facilitating quality control (157). The assessment tool was designed for the systematic review of prediction model studies and has been applied in many areas including breast cancer, kidney cancer, lymphocytic leukaemia, and oropharyngeal cancer (158)(159)(160)(161). We assessed the bias of the nine studies mentioned above using PROBAST and the results are shown in Table 2.…”
Section: Bias Assessment Based On Probastmentioning
confidence: 99%